Design, synthesis, biological activity evaluation and in silico studies of new nicotinohydrazide derivatives as multi-targeted inhibitors for Alzheimer's disease - TOK, FATİH; KAYMAKÇIOĞLU, BEDİA (My University, 2022)
A new series of 6-chloro-N\"-(substituted benzylidene)nicotinohydrazide were synthesized via condensation reactions between the corresponding hydrazides and aldehydes . All compounds were tested for their AChE and BuChE inhibitory activity. Compounds P5, P7, P9, P10 and P12 exhibited significant AChE inhibition potencies. Among them, compound P5 having para nitro substituent was found to be the most effective derivative against AChE with an IC50 value of 0.027 +/- 0.001 mu M. After that, the BACE-1 and beta-amyloid plaque inhibitory potencies of selected compounds P5, P7, P9, P10 and P12 were evaluated. Among them, compound P5 displayed the highest inhibition rate against the BACE-1 enzyme and beta-amyloid plaque. Molecular docking studies were carried out using both AChE and BACE-1 crystals to determine the compound\"s interactions with the enzyme\"s active sites. Furthermore, we evaluated the ADMET properties of compounds and their blood-brain barrier (BBB) permeation was also found to be high. (C) 2022 Elsevier B.V. All rights reserved.
Keywords: Kimya; Fizikokimya; Temel Bilimler; Chemistry; Physical Chemistry; Natural Sciences; KİMYA, FİZİKSEL; Temel Bilimler (SCI); CHEMISTRY, PHYSICAL; CHEMISTRY; Natural Sciences (SCI); Yüzeyler ve Arayüzler; Kimya (çeşitli); Genel Kimya; Fiziksel ve Teorik Kimya; Yüzeyler, Kaplamalar ve Filmler; Fizik Bilimleri; Surfaces and Interfaces; Chemistry (miscellaneous); General Chemistry; Physical and Theoretical Chemistry; Surfaces, Coatings and Films; Physical Sciences; Alzheimer's disease; Beta-amyloid plaque; Beta secretase; Cholinesterase inhibitors; Hydrazone; Molecular docking; BENZYL PYRIDINIUM MOIETY; ACETYLCHOLINESTERASE INHIBITORS; POTENTIAL ACETYLCHOLINESTERASE; CHOLINESTERASE-INHIBITORS; MONOAMINE-OXIDASE; MOLECULAR DOCKING; BINDING; HYBRIDS; VIEW; Alzheimer’s disease; Beta-amyloid plaque; Beta secretase; Cholinesterase inhibitors; Hydrazone; Molecular docking